KAPASITAS KELEMBAGAAN DINAS PEMADAM KEBAKARAN DALAM PENYELENGGARAAN LAYANAN DARURAT DI KOTA SEMARANG - Awang Luhur Nugroho; Maesaroh Maesaroh (Journal of Management and Public Policy, 2026)
The Semarang City Fire Service faces complex challenges in emergency service delivery, including a growing non-fire rescue workload, personnel shortages, and operational infrastructure constraints. This study aims to analyze the institutional capacity of the Fire Service in providing emergency services in Semarang City and to identify its enabling and inhibiting factors. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observation, and documentation. Informants were selected via purposive sampling, comprising organizational leaders, operational officers, and community service users. Data validity was ensured through source and method triangulation. The analytical framework draws on Grindle's (1997) institutional capacity theory, covering three dimensions: human resource development, organizational strengthening, and institutional reform. The findings reveal that institutional capacity is functional but not yet fully optimal. The human resource development dimension sustains operational service delivery, though constrained by personnel deficits, uneven training distribution, and psychological sustainability challenges. The organizational strengthening dimension is relatively robust structurally, yet impeded by limited renewal of strategic infrastructure and the absence of performance-based recognition. The institutional reform dimension performs optimally, evidenced by SOP updates, command center integration, and technology-based innovation. Enabling factors include collective commitment and conducive leadership, while the primary inhibiting factor is suboptimal regulatory responsiveness stemming from gaps between formal SOPs and dynamic field conditions.